1999
DOI: 10.1359/jbmr.1999.14.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, Antioxidant Vitamins, and the Risk of Hip Fracture

Abstract: Smoking increases the concentrations of free radicals, which have been suggested to be involved in bone resorption. We examined whether the dietary intake of antioxidant vitamins may modify the increased hip fracture risk associated with smoking. We prospectively studied 66,651 women who were 40-76 years of age. Forty-four of the cohort members who sustained a first hip fracture within 2-64 months of follow-up (n = 247) and 93 out of 873 age-matched controls were current smokers. Information on diet was obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
140
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(147 citation statements)
references
References 32 publications
3
140
1
3
Order By: Relevance
“…Our study, although much smaller and of a cross-sectional nature, is pointing in the same direction. Vitamin C is required for collagen crosslinking (Combs, 1998) and along with other antioxidant vitamins may serve to protect the skeleton from oxidative stress, especially from smoking (Melhus et al, 1999). Two recent population-based studies showed that use of long-term vitamin C supplements was beneficial for BMD in various skeletal sites (Leveille et al, 1997) and the effect was augmented by estrogen and Ca supplements use (Morton et al, 2001) in postmenopausal women.…”
Section: Multiple Regression Resultsmentioning
confidence: 99%
“…Our study, although much smaller and of a cross-sectional nature, is pointing in the same direction. Vitamin C is required for collagen crosslinking (Combs, 1998) and along with other antioxidant vitamins may serve to protect the skeleton from oxidative stress, especially from smoking (Melhus et al, 1999). Two recent population-based studies showed that use of long-term vitamin C supplements was beneficial for BMD in various skeletal sites (Leveille et al, 1997) and the effect was augmented by estrogen and Ca supplements use (Morton et al, 2001) in postmenopausal women.…”
Section: Multiple Regression Resultsmentioning
confidence: 99%
“…Trolox, a water-soluble vitamin E analogue, prevents osteoclast formation and bone loss by inhibiting both RANKL induction in osteoblasts and c-Fos expression in osteoclast precursors [42]. In an earlier study we established that an inadequate dietary intake of antioxidants increases considerably the risk of hip fracture in current smokers, whereas current smokers with a more adequate intake of antioxidants appear to have a fracture risk similar to that observed among never smokers [43], supporting the theory that oxidative stress has important effects on bone in man. A low intake of antioxidants has also recently been associated with an increased hip fracture risk in women [44,45].…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, epidemiological studies have provided evidence for the increased risk of bone fractures in patients with vitamin C deficiency as well as in smokers with insufficient intake of other antioxidants, such as vitamin E and selenium (6,8). The severity of antioxidant depletion and its relevance to the pathogenesis of multiple cell types and the ability of AA to induce differentiation of multipotent progenitor cells to osteoblasts, chondrocytes, cardiac myocytes, and dopaminergic neurons suggested that AA must be acting via other novel mechanisms to regulate cell differentiation at early stages and subsequent bone formation besides its well studied action to promote collagen synthesis/maturation and matrix protein interaction (14,15,31).…”
Section: Discussionmentioning
confidence: 99%